2010
DOI: 10.1186/1471-2229-10-84
|View full text |Cite
|
Sign up to set email alerts
|

Atypical response regulators expressed in the maize endosperm transfer cells link canonical two component systems and seed biology

Abstract: BackgroundTwo component systems (TCS) are phosphotransfer-based signal transduction pathways first discovered in bacteria, where they perform most of the sensing tasks. They present a highly modular structure, comprising a receptor with histidine kinase activity and a response regulator which regulates gene expression or interacts with other cell components. A more complex framework is usually found in plants and fungi, in which a third component transfers the phosphate group from the receptor to the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 59 publications
3
54
0
Order By: Relevance
“…Furthermore, the BETLspecific TF gene MRP-1, previously shown to be involved in regulation of BETL differentiation (Gómez et al, 2002(Gómez et al, , 2009, was also detected in M18 with a high MM score (1.00; Supplemental Data Set 4). This is consistent with its role as an activator of many BETLspecific genes, including BETL-1, BETL-9, BETL-10, BAP-2, MEG-1, TCRR-1, and TCRR-2 (Gómez et al, 2002(Gómez et al, , 2009Gutiérrez-Marcos et al, 2004;Muñiz et al, 2006Muñiz et al, , 2010. Therefore, these data suggest that MRP-1 acts as a major regulator of a subset of genes in the M18 coexpression module.…”
Section: Biological Processes Enriched In Coexpression Modules Of Thesupporting
confidence: 77%
See 4 more Smart Citations
“…Furthermore, the BETLspecific TF gene MRP-1, previously shown to be involved in regulation of BETL differentiation (Gómez et al, 2002(Gómez et al, , 2009, was also detected in M18 with a high MM score (1.00; Supplemental Data Set 4). This is consistent with its role as an activator of many BETLspecific genes, including BETL-1, BETL-9, BETL-10, BAP-2, MEG-1, TCRR-1, and TCRR-2 (Gómez et al, 2002(Gómez et al, , 2009Gutiérrez-Marcos et al, 2004;Muñiz et al, 2006Muñiz et al, , 2010. Therefore, these data suggest that MRP-1 acts as a major regulator of a subset of genes in the M18 coexpression module.…”
Section: Biological Processes Enriched In Coexpression Modules Of Thesupporting
confidence: 77%
“…These genes showed CS scores in the given compartments ranging from 0.47 to 0.99. Third, we summarized previously reported in situ hybridization or promoter activity data for cell-specific genes from the literature (Hueros et al, 1995(Hueros et al, , 1999Magnard et al, 2000Magnard et al, , 2003Serna et al, 2001;Woo et al, 2001;Gómez et al, 2002Gómez et al, , 2009Gutiérrez-Marcos et al, 2004;Wisniewski and Rogowsky, 2004;Balandín et al, 2005;Massonneau et al, 2005;Muñiz et al, 2006Muñiz et al, , 2010Royo et al, 2014) and also found these genes to have a relatively high range of CS scores (0.51 to 0.99). Altogether, these comprise 44 genes showing cell-specific expression in the endosperm (Supplemental Table 6).…”
Section: Identification Of Gene Sets Specifically Expressed In Each Omentioning
confidence: 85%
See 3 more Smart Citations